Relationship of Blood Pressure and White Matter Hyperintensity Burden With Level of and Change in Cognition in Older Black Adults. Issue 4 (22nd January 2022) - Lamar, Melissa; Fleischman, Debra A.; Leurgans, Sue E.; Aggarwal, Neelum; Yu, Lei; Kim, Namhee; Poole, Victoria; Han, S. Duke; Arfanakis, Konstantinos; Barnes, Lisa L.
ABSTRACT: Objective: Elevations in blood pressure (BP) and associated white matter hyperintensities (WMHs) are chronic comorbid conditions among older Black adults. We investigated whether WMHs modify the association between late-life BP and cognition within older Black adults. Methods: A total of 167 Black adults (age, ~75 years; without dementia at baseline) participating in neuroimaging studies at the Rush Alzheimer's Disease Center were evaluated for BP markers of cardiovascular health, including systolic BP, diastolic BP, pulse pressure, mean arterial pressure (MAP), and hypertension, and were assessed for global and domain-specific cognition at baseline and annually for up to 8 years. WMHs adjusted for intracranial volume were quantified at baseline. Results: Models adjusted for relevant confounders and the interaction of these variables with time revealed differential associations between BP markers and baseline cognition; however, only elevated diastolic BP predicted faster cognitive, that is, episodic memory, decline (estimate = −0.002, standard error = 0.0009, p = .002). Although WMH burden did not modify the association between diastolic BP and episodic memory decline, it did interact with diastolic BP to lower episodic memory at baseline (estimate = −0.051, standard error = 0.012, p = .0001); that is, greater WMHs combined with higher diastolic BP resulted in the lowest baseline episodic memory scores. A similar profile was noted for WMHs, MAP, and baseline episodic memory. Hypertension was neither associated with cognition nor modified by WMH burden after multiple comparisons correction. Conclusion: Late-life diastolic BP was associated with faster rates of episodic memory decline in older Black adults; together with higher WMH burden, it (and MAP) lowered the point at which individuals begin their course of decline toward pathological aging.